Effect of Metformin on Bcl-2/Bax Expression Ratio and Endometrial Implants: A Mouse Model in Endometriosis Study - Inu Mulyantoro; Oktoria Indrapraja; Widjiati Widjiati; Noor Pramono Noerpramana (Journal of Biomedicine and Translational Research, 2020)
Background: Endometriosis is a gynaecological disorder characterised by the presence of endometrial tissue outside the uterine cavity. Apoptosis, regulated by the balance of Bcl-2/Bax, plays an important role in the endometrial improvement. Metformin, an insulin sensitizer that is known to have beneficial effect in the endometriosis treatment, is expected to lower Bcl-2/Bax expression ratio and reduce endometrial implants.Objective: To explore the effect of metformin on the Bcl-2/Bax expression ratio and endometrial implant area of endometriosis-induced mice.Methods: This experimental study used 3-month old 33 BALB/c mice of endometriosis that were randomly and equally divided into three groups (P0, P1, and P2). On the 15th day, the P0 group was first terminated for Bcl-2/Bax examination and the size of endometrial implants. The P1 group was given aquabidest, whereas the P2 group was given metformin 4 mg/day for 14 days. The immunohistochemistry of Bcl-2/Bax expression were performed from cavum abdomen and pelvis peritoneal tissues of the mice and measured by the Remmele Scale Index, whereas the extracted mice’ endometrial implants were analysed with computer tracing method. All data normality test was calculated with Shapiro-Wilk test. The mean difference test of all groups was analysed using the one-way ANOVA test, whereas the mean difference test between groups was completed using the Unpaired T-test (LSD/Least Significance Difference).Results: The Bcl-2/Bax expression ratio and endometrial implant area in the P2 group were significantly lower compared to P0 and P1 (p<0.001). There were no significant differences in the Bcl-2/Bax expression ratio or endometrial implant area in P0 and P1 (p>0.05)Conclusion: Metformin may be a potential effective drug treatment for endometriosis by decreasing Bcl-2/Bax expression ratio and endometrial implants.